Reenacting the Past. An Essay on Götz and Meyer by David Albahari - Putyńska, Urszula (Poznańskie Studia Slawistyczne, 2017)
This paper is the analysis of Götz and Meyer (Gec i Majer, 1998) by David Albahari (b. 1948), the writer of Serbian and Jewish origin. His novel belongs to the Holocaust-literature and its metanarrative structure calls into question the problem of transferring radical historic moment into fiction. The article focuses on the interrelations between fiction and fact, imagination and history, as well as the traumatic experience recognized as the opportunity to identify with the experience of Holocaust victims. Albahariʼs novel proves that remembering of dramatic events from the past can be activated both by imagination and traumatic experience.